Pendampingan Pembuatan Video Profil untuk Konten Digital Marketing di Sekolah Islam Al Jannah - Wicaksono, Soetam Rizky; Nugroho, Didit Prasetyo; Setiawan, Rudy (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
The application of digital marketing requires planning in displaying the advantages possessed by the product, like a school with many features and facilities that can not only be displayed in one image. So, they need video media that can display what is owned by the school. This also applies to Al Jannah Islamic School, which is located in Pakis District, Malang Regency. Based on the results of observations, surveys, and brainstorming, the school agreed and supported the service team's activities to carry out the process of making school profile videos for the benefit of digital marketing. This community service activity aims to produce a video profile that can show the competitive advantage so that it can be displayed in various digital marketing channels. The steps taken consisted of: (1) observation and survey, (2) the process of shooting and finishing the video, and (3) brainstorming for publication. While the outputs produced are (1) digital marketing material content in the form of video profiles, (2) changes in the mindset of school managers in determining CA, (3) assistance in publications on various media channels, and (4) assistance for awareness in digital marketing. The conclusions of this activity are: (1) the results and outcomes are by the situation analysis, (2) the targets set at the beginning have been completed efficiently, and (3) the assistance provided by the team can help school managers.